1995
DOI: 10.1097/00000539-199502000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Packed Red Cells in Acute Blood Loss

Abstract: The purpose of this study was: 1) to define coagulation abnormalities in patients who receive red cell concentrates rather than whole blood for large volume blood loss (greater than 0.5 blood volume); and 2) to determine when coagulation abnormalities lead to increased bleeding in the massively transfused surgical patient. We studied 32 ASA physical status I or II patients (mean age 15.6 +/- 2.3 yr) who lost more than 50% of their blood volume during elective posterior spinal stabilization. Crystalloid solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…Data from adults and adolescents indicated that dilution of clotting factors becomes important when blood loss approaches 1.5 times EBV. The PT and PTT generally reach 1.5–2.0 times control values and fibrinogen may decrease to 75–125 mg/dl [26, 27, 32]. These values are very similar to those of group A patients.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Data from adults and adolescents indicated that dilution of clotting factors becomes important when blood loss approaches 1.5 times EBV. The PT and PTT generally reach 1.5–2.0 times control values and fibrinogen may decrease to 75–125 mg/dl [26, 27, 32]. These values are very similar to those of group A patients.…”
Section: Discussionmentioning
confidence: 75%
“…Fibrinogen and FVIII are acute phase reactants which complicates interpretation of their values. The clinical coagulopathy encountered can probably be explained as the summation of several mild factor deficiencies [27]. This interpretation is supported by the fact that PTT was the independent variable most significantly associated with blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Verdünnungskoagulopathie ist ein seit Langem bekanntes, klinisch relevantes Phänomen, das vor allem bei Volumenersatz ohne Gerinnungsfaktoren zu beobachten ist [10]. Es kann allerdings auch bei der alleinigen Verwendung von Plasma (vor allem über längere Zeit) auftreten, da während der Produktion von gefrorenem Frischplasma (fresh frozen plasma (FFP)) ein Teil der Gerinnungsfaktoraktivität verloren geht; mit FFP alleine kann daher bei anzustrebender Isovolämie keine gegenüber dem Normalzustand isoaktive Konzentration an Gerinnungsfaktoren erreicht werden [11].…”
Section: Unterschiedliche Pathophysiologische Hintergründe Von Koagulunclassified